COVID-19 and Undiagnosed Pre-diabetes or Diabetes Mellitus Among International Migrant Workers in Singapore - Louis Y. Tee; Sharifah Munirah Alhamid; Jeriel L. Tan; Theik Di Oo; Jaime Chien; Primavera Galinato; Seow Yen Tan; Shafi Humaira; Raymond Kok Choon Fong; Troy H. Puar; Wann Jia Loh; Anindita Santosa; et al. (Frontiers Media S.A., 2020)
Objective: Migrant workers, a marginalized and under-resourced population, are vulnerable to coronavirus disease 2019 (COVID-19) due to limited healthcare access. Moreover, metabolic diseases-such as diabetes mellitus (DM), hypertension, and hyperlipidemia-predispose to severe complications and mortality from COVID-19. We investigate the prevalence and consequences of undiagnosed metabolic illnesses, particularly DM and pre-diabetes, in international migrant workers with COVID-19.Methods: In this retrospective analysis, we analyzed the medical records of international migrant workers with laboratory-confirmed COVID-19 hospitalized at a tertiary hospital in Singapore from April 21 to June 1, 2020. We determined the prevalence of DM and pre-diabetes, and analyzed the risk of developing complications, such as pneumonia and electrolyte abnormalities, based on age and diagnosis of DM, and pre-diabetes.Results: Two hundred and fouty male migrant workers, with mean age of 44.2 years [standard deviation (SD), 8.5years], were included. Twenty one patients (8.8%) were diagnosed with pre-diabetes, and 19 (7.9%) with DM. DM was poorly controlled with a mean HbA1c of 9.9% (SD, 2.4%). 73.7% of the patients with DM and all the patients with pre-diabetes were previously undiagnosed. Pre-diabetes was associated with higher risk of pneumonia [odds ratio (OR), 10.8, 95% confidence interval (CI), 3.65-32.1; P < 0.0001], hyponatremia (OR, 8.83; 95% CI, 1.17-66.6; P = 0.0342), and hypokalemia (OR, 4.58; 95% CI, 1.52-13.82; P = 0.0069). Moreover, patients with DM or pre-diabetes developed COVID-19 infection with lower viral RNA levels.Conclusions: The high prevalence of undiagnosed pre-diabetes among international migrant workers increases their risk of pneumonia and electrolyte abnormalities from COVID-19.